(untitled) (MMIT Proceedings, 2025)
In this article, the main task facing the education system in today’s era of globalization and digital transformation is to educate a person who can meet modern requirements and needs. In this regard, traditional pedagogical approaches are changing, and interactive, innovative, and systematic methods are replacing them. Innovative approaches in the modern education system, in particular, integrative teaching methods based on the STEAM model, are analyzed from a scientific and pedagogical point of view. The essence of the new paradigm being formed in pedagogy - personality-oriented, active, and practical approaches - is revealed. The theoretical foundations of STEAM education, its place in interdisciplinary integration, and its role in the formation of creative thinking and problem-solving skills in students are highlighted.